IMPACT OF HEAT STRESS ON AGRO-MORPHOMETRIC AND FIBERRELATED TRAITS IN INDIGENOUS UPLAND COTTON GENOTYPES UNDER SEMI-ARID CONDITIONS - ASLAM, MZ; SAJJAD, MH; YOUSAF, MI; HUSSAIN, S; SHAH, SAS; BHATTI, MH; HUSSAIN, S; GHANI, A; IBRAR, I; AKRAM, M; RAZAQ, A; MEHBOOB, A; et al. (Biological and Clinical Sciences Research Journal, 2022)
To understand the impact of heat stress on agro-morphological and fiber quality-related traits in cotton, nine locally developed cotton genotypes were grown under heat stress conditions (Late sowing) at the cotton research station, Bahawalpur. Genotypes were laid-out under randomized complete block design (RCBD) in triplicates, where plant to plant and bed to bed distance was maintained as 30 cm and 75 cm, respectively. Data was collected from selected, guarded plants for agronomic as well as fiber quality-related traits. The resultsunveiled the presence of significant variations for studied traits under high temperature conditions. The correlation analysis revealed the significant association of seed cotton yield with plant population (0.403**), monopodial branches per plant (0.267**), fiber strength (0.070*), CLCuV incidence percentage (-0.475**), fiber length (-0.447**), nodes per plant (-0.186*), sympodial branches per plant (-0.186*), and fiber fineness (-0.077*). The multivariate approaches i.e., Principal component, biplot, and cluster analysis classify and characterize cotton genotypes on the basis of their heat tolerance capacity. Moreover, these multivariate analyses showed that BH-377, BH-272, and BH-283 were the most heat tolerant genotypes while BH-283 and BH-284 showed comparatively good CLCuV tolerance. Therefore, these genotypes should be recommended for sowing in heat and CLCuV effected areas of Pakistan after their large-scale, multilocation testing.